2009
DOI: 10.1021/bc9001618
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Cellular Uptake of Degradable and Water-Soluble Polyperoxides

Abstract: Water-soluble polyperoxides (PPs) as a new type of degradable and polymeric material were synthesized by the radical alternating copolymerization of sorbic derivatives containing a tetra(ethylene oxide) unit in the ester group using molecular oxygen. The obtained PPs showed a lower critical solution temperature (LCST)-type phase separation, and the transition temperature decreased according to the content of the hydrophobic ester group in the PPs. The PPs formed nanoaggregates with a diameter of 250-370 nm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Polyperoxides degrade highly exothermically in contrast to common polymers which usually degrade endothermically . Even though polyperoxides are very much sensitive towards heat, enzyme, light, acid, and base, they find significant academic and industrial usefulness as thermal and photo initiators for radical copolymerization, auto‐combustible fuels, curators in coating and molding compositions, dismantlable adhesion, drug delivery, etc. Recently, Sato and coworkers explored the thermal latent properties of 1‐phenyl‐3‐pyrazolidones (PhPs) with an active hydrogen towards their addition effect for sorbic ester‐based polyperoxides.…”
Section: Introductionmentioning
confidence: 99%
“…Polyperoxides degrade highly exothermically in contrast to common polymers which usually degrade endothermically . Even though polyperoxides are very much sensitive towards heat, enzyme, light, acid, and base, they find significant academic and industrial usefulness as thermal and photo initiators for radical copolymerization, auto‐combustible fuels, curators in coating and molding compositions, dismantlable adhesion, drug delivery, etc. Recently, Sato and coworkers explored the thermal latent properties of 1‐phenyl‐3‐pyrazolidones (PhPs) with an active hydrogen towards their addition effect for sorbic ester‐based polyperoxides.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Furthermore, polyperoxides and their derivatives, including branched and block copolymers, have been applied to various types of degradable functional materials, i.e., dismantlable (de-bondable) adhesives, 8,9 coatings for surface modication, 9,10 and biocompatible materials. 11,12 Matsumoto et al reported that the radical alternating copolymerization of 1,3-diene monomers with oxygen smoothly proceeded in solution under oxygen bubbling, i.e., at atmospheric pressure, in good yields. 13 Considering the fact that the synthesis of polyperoxides using general vinyl monomers requires a high oxygen pressure to increase the yield, 1 the synthesis of polyperoxides using 1,3-diene monomers is versatile, facile, and suitable for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Interpolymerization of vinylic monomers with O 2 appears to be quite ubiquitous, as no compound containing the vinyl or vinylidene group has been found which does not readily form a peroxide upon exposure to air under ordinary conditions, which have all been found to initiate polymerization . Kishore et al reported the preparation of oligo(peroxide)s with O 2 of typical vinylic monomers, including nonsubstituted, monosubsttituted, 1,1‐disubstituted (vinylidene), 1,2‐disubstituted vinylics, and conjugated dienes form oligo(peroxide)s under the induction of ultraviolet (UV) light, visible light, heat or radicals, or catalysis of Co II complexes, in bulk or organic solvents, while Matsumoto successfully attempted the radical alternating oxidative polymerization of conjugated dienes with O 2 , leading to degradable poly(peroxide)s …”
Section: Introductionmentioning
confidence: 99%